PENGARUH BRAND IMAGE DAN CUSTOMER VALUE TERHADAP CUSTOMER SATISFACTION DAN DAMPAKNYA PADA BRAND LOYALTY PT. ARINDO JAYA MANDIRI SEMARANG - Dila Nur Wahyuni Kumala Sari; Winarto - Winarto; Suryadi - Poerbo (Politeknik Negeri Semarang, 2018)
This study aims to analyze the influence of brand image and customer value on customer satisfaction and its impact on brand loyalty of freight forwarding services at PT. Arindo Jaya Mandiri Semarang. The population in this study is all customers of PT. Arindo Jaya Mandiri Semarang, they are 40 exporters. The data collection method is census that is total customer of PT. Arindo Jaya Mandiri Semarang, they are 40 exporters. The data are used the brand image, customer value, customer satisfaction, and brand loyalty collected derived from the questionnaire. The methods of analysis is using multiple linear regression and analysis path. The result of multiple linear regression of this research indicate the existence of positive and significant influence between brand image to customer satisfaction, the existence of positive and significant influence between customer value to customer satisfaction on regression equation stage 1. But for regression equation stage 2 that is positive and significant influence between brand Image of brand loyalty, the positive and significant influence between customer value on brand loyalty, and the positive and significant influence between customer satisfaction on brand loyalty. While the results of analysis of this research path shows that the brand image and customer value directly affect customer satisfaction in the analysis path of stage 1. As for the analysis path of stage 2 shows that customer satisfaction directly affect brand loyalty, brand image and customer value have no effect directly to brand loyalty through customer satisfaction.